Toward a normative model of rational argumentation for critical accounting discussions - Shapiro, B.P. (Accounting, Organizations and Society, 1998)
This article is based on the premise that the primary goal of a critical discussion in the accounting standard setting due process should be to reach conclusions by means of reasoned arguments. A normative model for achieving this goal is applied to some arguments made in recent accounting standard setting debates in the U.S. The model consists of eight maxims for advancing and defending arguments in a critical discussion in general and five presuppositions for a critical discussion about external financial reporting topics in particular. The normative model provides criteria for evaluating the validity of arguments, but it also is recognized that like all other language games the model does not (and cannot) carry within itself its own legitimation. The article concludes by considering how the standard setting debates can yield not only technical accounting outcomes but also changes in the nature of due process itself.